A STUDY OF DENOTATIVE AND CONNOTATIVE MEANINGS IN THE SONG LYRICS OF NDARBOY GENK - Anang Prasetya; Yuli Widiyono; Zuly Qurniawati (Department Javanese Literature and Language Education in Collaboration with Faculty of Teacher Training and Education Muhammadiyah University of Purworejo, 2026)
This study is motivated by the richness of meaning found in Javanese song lyrics, which may lead to various interpretations, particularly in the songs of Ndarboy Genk. Song lyrics function not only as entertainment but also as a medium for conveying emotional, social, and cultural messages through denotative and connotative meanings. The problem addressed in this study concerns how denotative and connotative meanings are represented in Ndarboy Genk’s song lyrics. This research aims to describe both types of meaning in five selected songs, namely Balungan Kere, Koyo Jogja Istimewa, Ojo Nangis, Anak Lanang, and Lanang Tenan. This study employed a descriptive qualitative approach. The data consisted of words, phrases, and sentences in the song lyrics containing denotative and connotative meanings. Data were collected through reading and note-taking techniques. The data were analyzed using a semantic approach by identifying, classifying, and describing meanings based on their contextual usage. The findings reveal that connotative meanings are more dominant than denotative meanings. Denotative meanings are used to convey literal realities directly, while connotative meanings express emotions, inner conflicts, social criticism, and Javanese cultural values. The use of figurative language further strengthens the connotative meanings within the lyrics. Overall, Ndarboy Genk’s songs represent values such as hard work, simplicity, responsibility, and the worldview of Javanese society. This study concludes that the song lyrics contain rich linguistic and cultural meanings worthy of semantic analysis.